Pendampingan Membaca AlQuran Menggunakan Metode Iqra’ di SDIT Nurul Ikhlas Kota Padang - Nazwan, Afif Putra; Kustati, Martin; Gusmirawati, Gusmirawati (Lembaga Yasin AlSys, 2023)
The purpose of mentoring reading the Quran using the Iqra' method for students of SDIT Nurul Ikhlas Padang City is because the potential of students at SDIT Nurul Ikhlas Padang City in reading the Quran is quite good, it's just that in practicing it there are still weaknesses and there are still mistakes in reading the Quran according to tajwed. So the researcher decided to carry out the purpose of mentoring reading the Quran using the Iqra' method for students of SDIT Nurul Ikhlas Padang City. The method used in this service is ABCD (Asset Based Community Development). It is an approach used in community empowerment by focusing on asset potential as a strength that is explored in community development. At this stage the pengabdi saw that the use of the iqra' method was very helpful for students in learning the Quran. Because this iqra' method is easier to understand and is familiar to students so it is easier to accept. After doing this service, it proves that the assistance in reading the Quran using the iqra' method has a good impact, students more easily know the hijaiyah letters and there is also an increase in the pronunciation of Makhorijul Letters.